The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/aln.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

Lung Inhomogeneities and Time Course of Ventilator-induced Mechanical Injuries

Abstract: Most of the computed tomography scan new densities developed in nonhomogeneous lung regions. The damage in this model was primarily located in the interstitial space, causing alveolar collapse and consequent high recruitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
69
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 26 publications
5
69
0
3
Order By: Relevance
“…An attractive possibility to tie the existence of a pressure range to an injury threshold is that local stress risers amplify the actual effect of applied pressure on local tissue tension-and locally inflicted power-that results from a given transpulmonary driving pressure. Damage would then propagate from those zones [10].…”
mentioning
confidence: 99%
“…An attractive possibility to tie the existence of a pressure range to an injury threshold is that local stress risers amplify the actual effect of applied pressure on local tissue tension-and locally inflicted power-that results from a given transpulmonary driving pressure. Damage would then propagate from those zones [10].…”
mentioning
confidence: 99%
“…Sustained high alveolar pressure distorts but does not dramatically injure epithelium until it cycles sufficiently often to lower pressure [9]. Moreover, VILI tends to propagate from points of mechanical heterogeneity, wherever they occur [3]. …”
mentioning
confidence: 99%
“…However, convincing investigations have uncovered at least three ways in which adverse tidal cycling pressures may injure the lung: (1) over distension of already inflated alveoli, with cellular distortion, epithelial wounding, and capillary stress fracture [1]; (2) tidal opening and closure with attendant (or causal) surfactant dysfunction, liquid bridge disruption, and high interfacial surface forces [2]; and (3) stress focusing/shear at points of micromechanical heterogeneity [3]. Over the years each has had a spokesperson for its primacy, backed by an impressive body of supportive scientific literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have shown that the inflamed lung releases cytokines into the blood stream, possibly leading to multi-organ failure [7,34]. There is extensive experimental evidence that mechanical ventilation itself can damage healthy lungs [15,19,26]. Several theories to explain the possible mechanisms of lung damage in healthy and diseased lungs have been proposed over the years [17,19].…”
Section: Introductionmentioning
confidence: 99%